2018
DOI: 10.1002/aenm.201702855
|View full text |Cite
|
Sign up to set email alerts
|

Proton Ion Exchange Reaction in Li3IrO4: A Way to New H3+xIrO4 Phases Electrochemically Active in Both Aqueous and Nonaqueous Electrolytes

Abstract: Progress over the past decade in Li‐insertion compounds has led to a new class of Li‐rich layered oxide electrodes cumulating both cationic and anionic redox processes. Pertaining to this new class of materials are the Li/Na iridate phases, which present a rich crystal chemistry. This work reports on a new protonic iridate phase H3+xIrO4 having a layered structure obtained by room temperature acid‐leaching of Li3IrO4. This new phase shows reversible charge storage properties of 1.5 e− per Ir atom with high rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Recently, a series of novel bulk protonated iridium phases H x IrO 3 and H x IrO 4 was uncovered via cation exchange in acidic conditions of the lithiated parent phases β-Li 2 IrO 3 and Li 3 IrO 4 , respectively. 61,62 For the H x IrO 4 phase, the cation exchange reaction drives a mild structural transition from the initial O3 stacking in Li 3 IrO 4 to a P3 stacking in H 3.4 IrO 4 , as shown in Figure 6a. In other words, the reaction is topotactic and allows the stabilization of the protonated iridate H 3.4 IrO 4 with a well-defined crystal structure (Figure 6b), which is of significant difference to the amorphous hydrated IrO x with a structure parent to the rutile IrO 2 phase formed on the surface of iridium metal oxides (Figure 3) or the amorphous hydrous IrO x formed from the oxidation of metallic Ir 63 .…”
Section: Extending the Stability Window Of Oer Catalysts In Acid By Tmentioning
confidence: 99%
“…Recently, a series of novel bulk protonated iridium phases H x IrO 3 and H x IrO 4 was uncovered via cation exchange in acidic conditions of the lithiated parent phases β-Li 2 IrO 3 and Li 3 IrO 4 , respectively. 61,62 For the H x IrO 4 phase, the cation exchange reaction drives a mild structural transition from the initial O3 stacking in Li 3 IrO 4 to a P3 stacking in H 3.4 IrO 4 , as shown in Figure 6a. In other words, the reaction is topotactic and allows the stabilization of the protonated iridate H 3.4 IrO 4 with a well-defined crystal structure (Figure 6b), which is of significant difference to the amorphous hydrated IrO x with a structure parent to the rutile IrO 2 phase formed on the surface of iridium metal oxides (Figure 3) or the amorphous hydrous IrO x formed from the oxidation of metallic Ir 63 .…”
Section: Extending the Stability Window Of Oer Catalysts In Acid By Tmentioning
confidence: 99%
“…Besides the main reflections, the weaker satellites that are visible in both powder XRD ( Figure S15) and electron diffraction patterns ( Figure S14 (Figure 6D), where the layers are systematically shifted by 1/3{110}. Similar shearing of close-packed oxygen planes to adopt the CrOOH structure [49] was observed by treating Li 2 MnO 3 [27] and Li 3 IrO 4 [21] in acid. Figure S16, where vibrations between 3000 cm -1 and 3400 cm -1 were found for the delithiated sample O1-"Li 0.75 H 1.25 RuO 3 " suggesting the presence of -OH groups within the structure [50] .…”
Section: Identification Of a New Phase With Greater Redox Currentsmentioning
confidence: 64%
“…Additionally, the absence of any noticeable differences between the open circuit potential for the as prepared and de lithiated sample also suggests no significant change in the Ru oxidations state ( Figure S17B). We note that while most studies have reported ion-exchange between Li + and H + in acidic solutions [13], [21]- [24] with a high proton (β-IrO 3 ) results in the formation of a protonated iridate structure, β-H 2 IrO 3 with the evolution of oxygen [51] as well as the work from Yang et al which shows that reaction of Li 2 MnO 3 in acidic, neutral and basic solutions leads to delithiation and proton incorporation into the structure [52] . However, it is virtually impossible to localize the hydrogen atoms in the O1-" Li 0.75 H 1.25 RuO 3 " using conventional laboratory XRD data.…”
Section: Identification Of a New Phase With Greater Redox Currentsmentioning
confidence: 78%
See 1 more Smart Citation
“…[ 41,46 ] Due to the incorporation of H + into the oxide layers to form a OHO bonding, the layer stacking sequence of the LRMO‐PAA material could undergo a structural change from O3 to a more stable P3 lattice. [ 46–48 ] In turn, this structural stabilization explains the cause for the protonation reaction taking place between PAA and LRMO. Thought the Li + /H + exchange reaction is negative to Li + storage capacity, the present 10 wt% PAA‐treated sample (LRMO = PAA) without structure change provides only limited Li + /H + exchange, which has little influence on the capacity of LRMO.…”
Section: Resultsmentioning
confidence: 99%